Analisis Hubungan Kondisi Perairan dengan Terumbu Karang di Desa Pemuteran Buleleng Bali - Alif, Sabil Al; Karang, I Wayan Gede Astawa; Suteja, Yulianto (Journal of Marine and Aquatic Sciences; Vol 3 No 2 (2017), 2017)
Coral reefs in the village of Pemuteran used for tourism activities. In the process of growth, the coral reef is strongly influenced by the water conditions both physical and chemical factors. This study aims to determine the characteristics of the water based physical and chemical factors, determine the percentage of coral cover, determine the relationship and influence the quality of the waters with coral reefs. Research carried out at Pemuteran Village in Mey 2016. The method used is linear transects and transect quadrant, principal component analysis to determine the effect of water quality parameters and relationships with coral reef. The results of the characteristics of the waters on physical factors, namely temperature 30 – 31°C, depth 4– 75 m, brightness 13 m, turbidity 1,2 –5,4 NTU, current velocity 0,1 – 0,4 m/s, and the substrate of sand. Based on chemical factors, namely salinity 31,25 – 31,55 ‰, pH 6,9–7,5, DO 5,5 – 6,4 mg/l, BOD5 0,57 – 0,76 mg/l, TSS 248–504 mg/l, nitrate 0,021 - 0,908 mg/l, and phosphate 0,065-0,95 mg/l. Coral cover percentage point 1 at 50,67%, points 2 at 65%, points 3 at 35%,points 4 at 85,33% and points 5 at 16,67%. While the point 6 - 10 there are no coral reefs. The main components of water quality that affect to the coral reef are the turbidity and substrate. The results show that the correlation of temperature and nitrate correlated very weakly. pH, DO, BOD5 and phosphate correlated enough. Salinity, current, and TSS strongly correlated. Depth, brightness, turbidity and substrate strongly correlate.
Keywords: water condition; coral reef; Pemuteran Vilage